PENGEMBANGAN MATERI AJAR TEKS CERITA FABEL BERBANTUAN FLIPBOOK KELAS VII SMP - Joice Sitinjak, Felicia; Harahap, Muharrina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to: (1) describe the process of developing flipbook-based fable story teaching materials for seventh-grade students at Putri Cahaya Private Junior High School in Medan, and (2) describe the validity of the developed teaching materials. The research employed the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. Due to time and research scope limitations, the study was conducted only up to the development stage. The instruments used included interviews, material validation questionnaires, design validation questionnaires, and validation by Indonesian language teachers. Data were analyzed using qualitative descriptive and quantitative descriptive techniques with a Likert scale. The development process produced flipbook-based fable story teaching materials that were tested through validation. The average score from material validators was 91% before revision and increased to 96% after revision, meeting the “highly suitable” criterion. The design validation obtained an average score of 88%, also categorized as “highly suitable.” In addition, validation by Indonesian language teachers resulted in an average score of 97%, indicating that the product was highly suitable for use. The teaching materials can be accessed through internet-connected devices at https://heyzine.com/flip-book/9d4307d6ae.html. The product consists of: (1) cover, (2) preface, (3) table of contents, (4) learning instructions, (5) learning outcomes and objectives, (6) introduction, (7) definition of fable texts, (8) characteristics, (9) structure, (10) language features, (11) intrinsic elements, (12) exercises, (13) sample fable texts, (14) structure analysis, and (15) instructional videos.